ChemInform Abstract: Hydroaminomethylation of Olefins with Aminomethyltrifluoroborate by Photoredox Catalysis. Issue 11 (March 2015) - Miyazawa, Kazuki; Koike, Takashi; Akita, Munetaka
Abstract The title reaction allows the introduction of a primary aminomethyl group onto electron‐deficient C=C bonds.